Ergonomic Evaluation of the Farm Women during Weeding (Indian Journal of Extension Education, 2011)
The study was carried out in Chhindwara district of Madhya Pradesh State to determine the time profile, weeding efficiency and physiological stress of women while performing the weeding activity. Weeding is an important agricultural unit operation. Delay and negligence in weeding operation affect the crop yield up to 30 to 60 per cent. With regard this, a manually operated Twin Wheel hoe was tested ergonomically in soybean and cotton field. The field experiment was carried out on 20 women each falling between the age group viz. 25 – 45 years. The results revealed that mean age of the respondents was 32.5 years with mean body height was 152.8 cm and mean weight was 45.2 kg. The weeding efficiency of the wheel hoe was satisfactory and it was easy to operate. Weeding efficiency was obtained up to 92.5 %. During weeding operation, Average heart rate of women was found to be 88.0 beats/min. as compared to local sickle as 90.5 beats/min by saving of 34% cardiac cost of worker. Women perceived drudgery reduction by 26.6 percent. . There was 50 percent reduction in number of labour needed per day in turn giving economic benefit of Rs. 300/day. The overall performance of the wheel hoe was promising.